Adult Spinal Deformities: Can Patient-Specific Rods Change the Preoperative Planning into Clinical Reality? Feasibility Study and Preliminary Results about 77 Cases. (10th July 2020) - Prost, S.; Pesenti, S.; Farah, K.; Tropiano, P.; Fuentes, S.; Blondel, B.
Abstract : Surgical management of adult spinal deformities remains challenging, and one of the major goals is to restore sagittal alignment. Spinal rods used for posterior fixation are usually delivered straight and bended manually during surgery. This manual bending can be responsible for undercorrection of the deformity. In the last years, prebended patient-specific rods have been developed and might be a valuable tool in order to optimize surgical results. The objective is therefore to use the time between surgical decision and operative room in order to realize a precise surgical planning and obtain patient-specific rods. We describe here the planning process and our preliminary experience with patient-specific rods in the management of adult deformity about 77 cases. On the 77 cases, PSR were used without further modifications of the shape. Based on 3-month postoperative evaluation, a significant decrease of sagittal vertical axis (−41%, p < 0.0001 ) and pelvic incidence-lumbar lordosis (−62%, p < 0.0001 ) was reported. Pelvic tilt was not significantly corrected, except in patients with Parkinson's disease. In this subgroup of patients, measurements revealed a significant correction of SVA and PI-LL (−53%, p = 0.005, and −81%, p < 0.0001, respectively) but also of PT (−23%, p < 0.001 ). The use of PSR, in our experience, was feasible and provided satisfactory short-term results. It can be a valuable tool in the management of adult spinal deformities. Further studies will be needed in order to confirm these preliminary results.